(untitled) (Вестник Военного института Сухопутных войск имени С. Нурмагамбетова, 2025)
For the successful prevention of terrorism and extremism among young people, it is necessary to have scientific and methodological support and create suitable socio-pedagogical conditions in educational institutions. The article is devoted to modeling the process of developing anti-terrorist consciousness among young people, identifying the conceptual and technological components of this process. Based on the analysis of philosophical and psychological and pedagogical literature, the essence and content of anti-terrorist consciousness are substantiated, the process of developing anti-terrorist consciousness is substantiated, measures for the development of the phenomenon under study are proposed: monitoring, studying the social well-being of young people, as well as the study of communication deviations both within study groups and with other people. The authors emphasize the importance of fostering tolerance and countering influences that cause fear and alienation from other peoples and cultures. This will help young people develop the skills of independent, critical thinking and forming judgments based on moral values.